UNSUR DAPAT MERUGIKAN KEUANGAN NEGARA ATAU PEREKONOMIAN NEGARA PADA PERTANGGUNGJAWABAN TINDAK PIDANA KORUPSI - S. Serbabagus (Lex Journal: Kajian Hukum & Keadilan, 2017)
The existence problem of corruption in Law Number 31 Year 1999 as amended by Law Number 20 Year 2001 is the formulation of element "may harm the state finance or state economy" in Article 2 paragraph (1) and article 3 which causes the emergence of The debate on understanding the word "can harm" it. The purpose of writing in this is to know the qualification of elements can harm the state finance or the state economy on corruption crime as well as to know the proof of the element can harm the state finance or state economy on corruption criminal law. From the main result of writing can be concluded that Element "can harm state finance or state economy" represent potential loss of state finance or state economy in order to fulfill the element "may harm the state finance or state economy" does not necessarily have suffered losses, but the element of state losses must still be proven and must be calculated, although as an estimate or though it has not yet occurred and the calculation shall be determined by the expert.